Optimizing Cash Waqf to Support the Free Nutritional Meal Program: A Study at Baitul Mal Aceh - Muksal Muksal; Fiqah Rauthen (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2025)
This study aims to analyze the role of Baitul Mal Aceh (BMA) in managing and optimizing cash waqf to support education programs and the Free Nutritious Meals (MBG) initiative, which is designed to improve children’s nutrition, school attendance, and learning outcomes. These objectives align with the fundamental goals of waqf as a sustainable social instrument that preserves life and intellect. The returns generated from cash waqf can be allocated to finance daily meal provision, reduce the financial burden on low-income families, and ensure the long-term continuity of the MBG program without relying solely on annual government budgets. Using a qualitative approach, this study employs in-depth interviews with BMA managers and academics, supported by document analysis. The findings reveal that although BMA holds strategic potential to develop cash waqf for supporting MBG, its implementation remains limited due to regulatory constraints, low waqf literacy, and the absence of digital-based fundraising infrastructure. Conversely, Aceh’s strong philanthropic culture, supportive regional regulations, and the growing need for sustainable social financing present significant opportunities. Overall, cash waqf demonstrates substantial potential as a sustainable Islamic public finance instrument capable of ensuring the continuity of education and nutrition programs while contributing to social welfare and the achievement of the Sustainable Development Goals (SDGs)